2007
DOI: 10.1080/02770900701209806
|View full text |Cite
|
Sign up to set email alerts
|

Protection Against Exercise-Induced Bronchoconstriction Two Hours After a Single Oral Dose of Montelukast

Abstract: The objective of this double-blind cross-over study was to evaluate montelukast for the prevention of exercise-induced bronchoconstriction (EIB). Sixty-two patients with EIB (post-exercise decrease in forced expiratory volume in 1 second (FEV(1)) > or = 20% at pre-randomization) were randomized to montelukast 10 mg or placebo, followed by exercise-challenge 2, 12, and 24 hours postdose. The primary endpoint was the maximum percent-fall in FEV(1) (from pre-exercise FEV(1)) during 60 minutes after exercise-chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 24 publications
1
30
0
1
Order By: Relevance
“…It also improved postexercise recovery from EIB [40•]. A second similarly designed study of 62 patients with EIB showed similar effi cacy at 2 hours after a single dose of montelukast compared with placebo (11.7% for montelukast vs 17.5% for placebo; P ≤ 0.001) but failed to show a statistically signifi cant difference at 12 and 24 hours, in part because EIB severity waned in the placebo group at 12 and 24 hours after placebo administration [41]. A study of 19 children with EIB who were using an inhaled corticosteroid (ICS) demonstrated reduced EIB severity relative to placebo at 12 hours after the single dose but not 2 or 24 hours after the single dose [42].…”
Section: Acute Effects Of Leukotriene Modifi Ers On Eib Severitymentioning
confidence: 96%
“…It also improved postexercise recovery from EIB [40•]. A second similarly designed study of 62 patients with EIB showed similar effi cacy at 2 hours after a single dose of montelukast compared with placebo (11.7% for montelukast vs 17.5% for placebo; P ≤ 0.001) but failed to show a statistically signifi cant difference at 12 and 24 hours, in part because EIB severity waned in the placebo group at 12 and 24 hours after placebo administration [41]. A study of 19 children with EIB who were using an inhaled corticosteroid (ICS) demonstrated reduced EIB severity relative to placebo at 12 hours after the single dose but not 2 or 24 hours after the single dose [42].…”
Section: Acute Effects Of Leukotriene Modifi Ers On Eib Severitymentioning
confidence: 96%
“…The most effective therapy for EIA is regular use of ICS [122]. Early use of leukotriene inhibition may be equally effective [149,150].…”
Section: Subgroups With Treatment Implicationsmentioning
confidence: 99%
“…Leukotriene modifiers such as montelukast are effective in treating EIB when given daily or 2 hours prior to exercise [41]. There has been no development of tolerance when leukotriene modifiers are given daily [42].…”
Section: Treatmentmentioning
confidence: 99%